2010
DOI: 10.1111/j.1474-9726.2010.00590.x
|View full text |Cite
|
Sign up to set email alerts
|

Metabolomics‐based systematic prediction of yeast lifespan and its application for semi‐rational screening of ageing‐related mutants

Abstract: SummaryMetabolomics -the comprehensive analysis of metabolites -was recently used to classify yeast mutants with no overt phenotype using raw data as metabolic fingerprints or footprints. In this study, we demonstrate the estimation of a complicated phenotype, longevity, and semirational screening for relevant mutants using metabolic profiles as strain-specific fingerprints. The fingerprints used in our experiments are profiled data consisting of individually identified and quantified metabolites rather than r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
38
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 59 publications
(43 citation statements)
references
References 25 publications
5
38
0
Order By: Relevance
“…Multivariate Analysis-GC-MS data were processed as described previously (20) and judged by principal component analysis (PCA) using the SIMCA-p ϩ program (version 12.0.1, Umetrics, Malmö, Sweden).…”
Section: Methodsmentioning
confidence: 99%
“…Multivariate Analysis-GC-MS data were processed as described previously (20) and judged by principal component analysis (PCA) using the SIMCA-p ϩ program (version 12.0.1, Umetrics, Malmö, Sweden).…”
Section: Methodsmentioning
confidence: 99%
“…In our previous study, metabolic fingerprinting revealed a correlation between lifespan and metabolic profile [12,13]. To investigate a possibility that heterozygous deletion of FHL1, RAP1, REB1, and MCM1 changes cellular metabolisms to shorten lifespan, the whole-cell metabolite levels were surveyed by 1 H-NMR-based metabolomic analysis.…”
Section: Deletion Of Fhl1 Changed 1 H-nmr Metabolic Profilementioning
confidence: 99%
“…In a previous study, mass spectrometry-based metabolome analysis of intracellular compounds (fingerprinting) revealed a correlation between the replicative lifespan and metabolic profiles, and the prediction model of yeast lifespan was constructed based on the metabolome data [12]. The metabolic profiles presumed that UGA3 gene encoding a transcription factor (TF) for g-aminobutyric acid metabolic pathway genes was involved in lifespan regulation, followed by identification of the Uga3p-targeted UGA1 and GAD1 metabolic enzyme genes [12,13]. Furthermore, metabolome analysis of aging yeast cells showed metabolic changes at the early stage of Abbreviations: TF, transcription factor; NMR, nuclear magnetic resonance; RTqPCR, reverse transcription-quantitative polymerase chain reaction; OPLS, orthogonal projections to latent structures.…”
Section: Introductionmentioning
confidence: 99%
“…14) "By the way, phenotype in the conventional genetics has been de ned as a 'qualitative' feature, but not 'quantitative' one." erefore classical phenotype analysis is similar to a "yes/no" problem about existence of quantitative phenotype.…”
Section: Strategic Seeking Of Life-span Relat-ed Genes Of Budding Yeastmentioning
confidence: 99%